Pengaruh Sosialisasi Dakwah terhadap Perilaku Masyarakat di Rumah Yatim Mulia - Anis Nadhja Azizah; Edy Sarwoko; Jumi Jumi; Yapan Yapan (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
Da'wah as a process of conveying Islamic values cannot be separated from the dynamics of the behaviour of the community that is its object. This study aims to analyse the relationship between da'wah and community behaviour in a sociological perspective, as well as identify da'wah strategies that are in accordance with the social context that continues to develop. Understanding the character of community behaviour is the main key in designing communicative, relevant, and solutive da'wah methods. This study aims to analyse the influence of da'wah socialisation on changes in community behaviour, both children and adults. Dawah socialisation is carried out through lectures, routine coaching, and structured religious activities. With a descriptive-qualitative approach, data were collected through observation and interviews with administrators and beneficiaries. The results showed that da'wah socialisation positively contributed to the increase of religious awareness, discipline, and social care of the surrounding community.